Who Accused Whom of What? The Outbreak of the “Arian” Controversy (Johns Hopkins University Press, 2023)
This article aims to reconstruct the outbreak and initial parameters of the so-called Arian crisis. To do that, it divides ancient sources into two different groups: 1) the sources that reproduce or depend on the polemical narrative of Athanasius and 2) the documents contemporary to the events, which are quoted in ancient works. Since Athanasius’s narrative is one-sided and retrospective, the article reconstructs the beginning of the controversy by giving effective priority to documents contemporary to the events over accounts coming from the bishop of Alexandria. Thus, the first part of the article studies the outbreak of the dispute according to ancient sources; therefore, it reconstructs the beginning of the controversy in light of the sources coming from Athanasius, analyzes the chronology of the contemporary documents, and finally reviews the outbreak of the crisis by giving hermeneutical priority to contemporary documents. The second part studies the initial theological parameters of the debate, namely, the theologies of Alexander and Arius, and the “Arian” theology according to Alexander. The last part of the article addresses the ecclesiastical dimension of the controversy, that is, the nature of “the group around Arius” and the institutional setting of the conflict. The conclusion re-examines the outbreak of the Arian crisis.